If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 6p + -1 = p + 20 Reorder the terms: -1 + 6p = p + 20 Reorder the terms: -1 + 6p = 20 + p Solving -1 + 6p = 20 + p Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-1p' to each side of the equation. -1 + 6p + -1p = 20 + p + -1p Combine like terms: 6p + -1p = 5p -1 + 5p = 20 + p + -1p Combine like terms: p + -1p = 0 -1 + 5p = 20 + 0 -1 + 5p = 20 Add '1' to each side of the equation. -1 + 1 + 5p = 20 + 1 Combine like terms: -1 + 1 = 0 0 + 5p = 20 + 1 5p = 20 + 1 Combine like terms: 20 + 1 = 21 5p = 21 Divide each side by '5'. p = 4.2 Simplifying p = 4.2
| 6(x+8)=7X+3 | | 27*x=1800 | | 6(X+8)=7x-3 | | -6+3X-3Y=0 | | 0=-Y+X-4 | | -3+2X=Y | | 7x+5x+10= | | y+5=-10(X-1) | | 18x^2-47x-56=0 | | 3+(5a+5)=35 | | -1-9x=9x+19 | | 15*x^10=67 | | 7(4b-1)=-3b-2 | | 3(2m-10)=2m+10 | | 20=14m-9+3(5m) | | 17-x=3x-7 | | 8x-6=-2(6x+4)+2x | | x^5-4x^4+x^3+2=0 | | 47+3=40 | | X=45 | | y=4-xsqaured | | 16y^2+28=0 | | 10x+11y= | | x^4+5x^2+49=0 | | -(-x-5)+5(x-9)=2(x+8)-2x+5 | | 3n+2=9 | | 2x=3(1-x)-(x-1) | | 2x^3-12x^2+24x-2=0 | | 3x-(x-2)=(2x-1)(-3x+9) | | (2x-1)(-3x+9)=0 | | 2(c-2)whenc=7 | | 3x-1=4(2x-5) |